THE TEACHING OF READING COMPREHENSION BY USING A SMALL GROUP DISCUSSION (SGD) AT THE FIRST YEAR STUDENTS OF SENIOR HIGH SCHOOL - Jihan Harfina Christianti; Dian Arief Pradana; St. Shabibatul Rohmah (RADJA PUBLIKA, 2023)
The purpose of this study was to determine whether the use of discussion methods in small groups contributed to significant improvements in students' reading comprehension. In this study, we used X IPA 1 with 36 students as a sample. A one-group pretest-posttest design is used in this study. The results showed that using small group discussion techniques improved students' reading comprehension. Students averaged 68.8 on the pretest and 72.2 on the posttest. The outcome of the Independent Samples T-Test used in hypothesis testing serves as evidence. The significant value is less than 0.05 (0.00 <05),), indicating a significant difference in the results of this study. As a result, the research hypothesis is accepted. This shows that the small group discussion approach to teaching and learning in SMAN 1 Rogojampi is very effective in improving students' reading comprehension.